ONLINE MARKETING COMMUNICATION STRATEGIES MUSLIM FASHION PRODUCTS â€œKAWAN MUSLIM - Latif Pratama, Mhd.; Alfikri, Muhammad (Universitas Dharmawangsa, 2022)
Kawan Muslimâ€ is one of the Muslim fashion brands playing in the online market that has been able to grow rapidly with a rating of almost 5 stars on each of its products. The purpose of this study is to determine the online marketing communication strategy carried out by Kawan Muslim Muslim clothing in increasing brand awareness. The research type uses a descriptive type of qualitative approach with qualitative descriptive research methods. Data collection techniques carried out by interviews and observations. The technique of checking the validity of data using triangulation. Kawan Muslim is a Muslim fashion brand that chooses the online route in marketing its products. The results of the study explained that the marketing communication strategy carried out by Kawan Muslim is to focus on promotions carried out in various social media line-ups at this time. In conclusion, the marketing strategy has a promotional focus on sales and advertising. It is proposed to have a person in charge who specifically takes care of online.Â